Hacienda Pioneer Valley View proposed school building - Gordon, John C. (photographer):::Creator::::::::::::
Photograph of an front elevation of a proposed school building in Santa Clara County, California. Printed on recto: "Proposed school building Santa Clara Co., Cal., Hacienda Pioneer Valley View, Elementary Union School District."